The relationship among customer operant resources, online value co-creation and electronic-word-of-mouth in solid waste management marketing. (1st March 2020) - Frempong, Joseph; Chai, Junwu; Ampaw, Enock Mintah; Amofah, Dennis Owusu; Ansong, Kwame Wadei
Abstract: In recent times, waste management has engaged the attention of governments, policy makers, and academics as it has ramifications for the health and well-being of citizens, the environment, and the economy. In this regard, waste management firms and policy makers are employing strategic approaches to waste management efforts by empowering relations among various stakeholders to innovate. Thus, customer and stakeholder value co-creation is one such strategic approach waste management firms can adopt to create value and to brand. Previous studies of co-creation in waste management are largely broad in perspective. The purpose of this study is, therefore, to assess the relationship among customer operant resources, online value co-creation and digital branding through electronic word-of-mouth in the Ghanaian waste collection industry. Using the positivist research paradigm approach, a structured questionnaire was used to collect data from customers through social media platforms. Hierarchical multiple regression was used to test the hypotheses. The relationships among customer operant resources, co-creation and electronic word-of-mouth were all significant. Customer value co-creation positively mediates between customer operant resources and electronic word-of-mouth. Firm web-based platforms also positively moderate the effects of customer operant resources on customer online value co-creation. The results of the study can guide management of the firms to design appropriate strategic and educational programs for the customers. This study has advanced knowledge on the importance of customer operant resources in waste management value co-creation by demonstrating the degree of impact of each of these customer resources. Highlights: Customer operant resources have become imperative resources for firm value co-creation in a digitalized business world. Solid waste collection is a service that requires the active involvement of beneficiaries to ensure efficiency and effectiveness. Householders were surveyed to examine the essence of co-creation in solid waste management. The relationship among customer operant resources, customer value co-creation, and customer advocacy is statistically significant. Customer value co-creation is a strategic decision making and marketing approach.